(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The study was aimed to trace out antihyperglycemic potentials of Nymphaea alba leaves using in vitro and in vivo approaches. In, in vitro study, determination of IC50 of Nymphaea alba extracts was done using α-amylase and α-glucosidase inhibition assay. In α-amylase, Nymphaea alba methanol extract (NAME) exhibited maximum inhibition 56.77±1.23% at 125µg/ml in comparison to 66.7±0.94 % of standard acarbose. In α-glucosidase, NAME exhibits 59.89±0.92, while standard acarbose showed 70.31±1.25 % inhibition. The in vivo study was performed on diabetic rats, made diabetic by Streptozotocin. 200mg/kg and 400mg/kg NAME was administered orally, which significantly (